Antitumor Activity of Isalpinin from Paphiopedilum dianthum on Non-Small Cell Lung Cancer Cell Lines - Phisit Pouyfung; Nonthalert Lertnitikul; Hua Bai; Achitphol Chookaew; Varisa Pongrakhananon; Piriya Chonsut; Suwichak Chaisit (Molecules, 2025)
Lung cancer is a leading cause of cancer-related deaths globally, with current treatments having significant limitations, including drug resistance, metastasis, and tumor heterogeneity. This study investigated the anticancer potential of isalpinin, a flavonoid isolated from Paphiopedilum dianthum, against non-small cell lung cancer (NSCLC) cell lines A549, H23, and H460. Isalpinin significantly inhibited NSCLC cell viability in a dose- and time-dependent manner; H23 and H460 cells showed greater sensitivity (IC50 a ~ 44 μM at 48 h) compared to A549 cells (IC50 82 μM). Isalpinin suppressed proliferation, migration, and anchorage-independent growth, particularly in H23/H460 cells. Mechanistically, it induced apoptosis via increased ROS production and Bcl-2 downregulation, particularly in H23 and H460 cells. In a molecular docking analysis, isalpinin was found to directly bind to the ATP-binding pocket of AKT1, as confirmed by reduced Akt/GSK3β phosphorylation. These results suggest that isalpinin showed a potent multi-target natural compound against NSCLC that disrupts the key hallmarks of malignancy and pro-survival signaling. However, its subtype-specific efficacy warrants further in vivo studies and an investigation of combinatorial therapeutic approaches to elucidate its clinical potential.